Damaged forests provide an opportunity to mitigate climate change. Issue 1 (3rd April 2013) - Lamers, Patrick; Junginger, Martin; Dymond, Caren C.; Faaij, André
Abstract British Columbia (BC) forests are estimated to have become a net carbon source in recent years due to tree death and decay caused primarily by mountain pine beetle (MPB) and related post‐harvest slash burning practices. BC forest biomass has also become a major source of wood pellets, exported primarily for bioenergy to Europe, although the sustainability and net carbon emissions of forest bioenergy in general are the subject of current debate. We simulated the temporal carbon balance of BC wood pellets against different reference scenarios for forests affected by MPB in the interior BC timber harvesting area using the Carbon Budget Model of the Canadian Forest Sector (CBM‐CFS3). We evaluated the carbon dynamics for different insect‐mortality levels, at the stand‐ and landscape level, taking into account carbon storage in the ecosystem, wood products and fossil fuel displacement. Our results indicate that current harvesting practices, in which slash is burnt and only sawdust used for pellet production, require between 20–25 years for beetle‐impacted pine and 37–39 years for spruce‐dominated systems to reach pre‐harvest carbon levels (i.e. break‐even) at the stand‐level. Using pellets made from logging slash to replace coal creates immediate net carbon benefits to the atmosphere of 17–21 tonnes C ha−1, shortening these break‐even times by 9–20 years and resulting in an instant carbon break‐even level on stands most severely impacted by the beetle. Harvesting pine dominated sites for timber while using slash for bioenergy was also found to be more carbon beneficial than a protection reference scenario on both stand‐ and landscape level. However, harvesting stands exclusively for bioenergy resulted in a net carbon source unless the system contained a high proportion of dead trees (>85%). Systems with higher proportions of living trees provide a greater climate change mitigation if used for long lived wood products.